Sawadaea taibaishanensis sp. nov. (Erysiphales, Erysiphaceae): a powdery mildew of Acer from China - Peng, Zijia; Yu, Zhongdong (Phytotaxa, 2026)
The genus Sawadaea (Erysiphales, Erysiphaceae) comprises obligate parasitic fungi that cause powdery mildew diseases primarily on maples (Acer spp.). During a mycological survey in the Qinling Mountains, China, distinctive powdery mildew specimens were collected from leaves of Acer stachyophyllum subsp. betulifolium. To elucidate its taxonomic status, we conducted comprehensive morphological characterization using light microscopy and molecular phylogenetic analyses based on a concatenated ITS and LSU dataset. The fungus is distinguished from all previously described Sawadaea species by its unique chasmothecia bearing numerous dichotomously to trichotomously branched appendages with up to 12 ultimate branchlets. Phylogenetically, the specimens form a monophyletic clade with strongly supported values of ML/MPBS = 100% and BPP = 1.0, within the genus Sawadaea. Based on this congruent morphological and phylogenetic evidence, the fungus is formally described herein as a new species, Sawadaea taibaishanensis sp. nov.